“BioClay™”: One Step toward the Sustainable and Novel Plant Protection Method - Vaddoriya, Hrushikesh K.; Shelar, Vaibhav Babasaheb; Pampaniya, Anil; Panwala, Anvi (International Journal of Economic Plants, 2024)
World peace depends on global food security with finite resources. In addition to these finite resources, biotic stress poses an additional threat to global food security. Plant breeding is an effective tool for combating biotic stresses. Scientists have developed various genetically modified crops tolerant to plant diseases and insects. However, Development of multiple biotic stress-tolerant cultivars through conventional breeding is a tedious and long-term process. However, the usage of pesticides is a rapid and short-term solution to fight against biotic stresses, but it will result in pesticide residues, which threaten the agricultural product’s export to foreign markets and human health. To meet the UN Sustainable Development Goal 2030, sustainable solutions are needed to stay strong against these biotic stresses. In recent times, scientists have been approaching biotechnology and nanotechnology to counter biotic stresses. This study is solely based on the breakthrough innovation of “BioClay™” or dsRNA-LDH complex as a sustainable and eco-friendly potential for plant protection. “BioClay™” or dsRNA-LDH complex is used to induce RNAi and sustain delivery of dsRNA, which is a sustainable alternative to chemical usage. This technology is found to be prominent against various biotic stresses in plants. This information will be helpful to scientists for further research to fill the gap between previous research. This study also focuses on the future direction of “BioClay™” or dsRNA-LDH complex technology.